Study on heat flux variation due to temperature humdity and ventilation flow for a model house for a certain continuous period - Farizul Amri Mohammad (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The aim of this study was to understand and establish passive cooling method in hot humid climates. This is because Malaysia receives high temperature with low air velocity that can influence the thermal comfort. The review was focused on the fundamental of passive cooling, thermal comfort and existing pass cooling method